How can we optimise health technology assessment and reimbursement decisions to accelerate access to new cardiovascular medicines?. (15th October 2022) - Cowie, Martin R.; Bozkurt, Biykem; Butler, Javed; Briggs, Andrew; Kubin, Maria; Jonas, Adrian; Adler, Amanda I.; Patrick-Lake, Bray; Zannad, Faiez
Abstract: Regulatory approvals of, and subsequent access to, innovative cardiovascular medications have declined. How much of this decline relates to the final step of gaining reimbursement for new treatments is unknown. Payers and health technology assessment (HTA) bodies look beyond efficacy and safety to assess whether a new drug improves patient outcomes, quality of life, or satisfaction at a cost that is affordable compared to existing treatments. HTA bodies work within a limited healthcare budget, and this is one of the reasons why only half of newly approved drugs are accepted for reimbursement, or receive restricted or "optimised" recommendations from HTA bodies. All stakeholders have the common goal of facilitating access to safe, effective, and affordable treatments to appropriate patients. An important strategy to expedite this is providing optimal data. This is demonstrably facilitated by early (and ongoing) discussions between all stakeholders. Many countries have formal programmes to provide collaborative regulatory and HTA advice to developers. Other strategies include aligning regulatory and HTA processes, increasing use of real-world evidence, formally defining the decision-making process, and educating stakeholders on the criteria for positive decision making. Industry should focus on developing treatments for unmet medical needs, seek early engagement with HTA and regulatory bodies, improve methodologies for optimal price setting, develop internal systems to collaborate with national and international stakeholders, and conduct post-approval studies. Patient involvement in all stages of development, including HTA, is critical to capture the lived experience and priorities of those whose lives will be impacted by new treatment approvals. Graphical abstract: Unlabelled Image